ANALYSIS OF GRAMCI'S HEGEMONY THEORY IN THE SHORT STORY "ROBOHNYA SURAU KAMI" BY AA NAVIS - Rangkuti, Mhd Alfin; Septiandy, Muhammad Fichri; Wardanah, Jeihan Fitrah; Angkat, Puriandari; Astuti, Widia (LUMBUNG AKSARA, 2023)
The short story "Robohnya Our Surau" by A.A. Navis describes the story of a surau keeper known as Grandpa, as well as how social changes and shifts in religious values ​​affect people's lives. Using the framework of Antonio Gramsci's theory of hegemony, this analysis examines three main elements: ideology, culture and beliefs contained in the story. This short story shows how a strong religious ideology is the basis for Grandpa in living his life, but at the same time, this ideology is also challenged by the social realities faced by the surrounding community. Cultural shifts can be seen through changes in people's attitudes towards the surau and Grandfather, as well as the emergence of figures such as Ajo Sidi who bring new, critical perspectives.